Sustainability Discourse and Influencer Networks in Plant-Based and Dairy Protein Milk Conversations: A Social Network Analysis and Sentiment Mining Study on X (Twitter) - Abiali Al-Ikhsan; Asep Miftahuddin; Eka Surachman; Yoga Perdana; Budhi Pamungkas Gautama; Arciana Damayanti (CV. Media Digital Publikasi Indonesia, 2026)
This study examines the discourse of sustainability and social media influencers’ networks concerning X (Twitter) conversations involving plant-based milk and dairy milk with regard to how these two affect consumer perceptions and product marketing. Methods for quantitative and explorative research in combination with social network analysis (SNA) and sentiment mining were applied. The source of data for this research was based on 223 X (Twitter) posts retrieved from SocialX from December 1, 2025, to May 5, 2026. Sentiment analysis was performed using the lexicon approach, which was further weighted based on engagement measures, whereas SNA was performed based on the centrality and community structure of the networks. The results indicate that sustainability discourse is predominantly neutral or positive in nature, with a slightly positive sentiment score. The network demonstrates high levels of centrality, where the nodes with high levels of influence have an effect on information dissemination. The sentiment trends are marked with high levels of variability and occasional occurrences of negative sentiments, which implies that the discourse is driven by certain events. The emotion analysis shows that the emotions expressed are positive in nature but are not varied. The present study makes an important contribution to the literature in terms of incorporating the concepts of sentiment analysis together with social network analysis to explore the role of sustainability discourse in a competitive product environment.